The role of indium in the activation of aluminum alloy galvanic anodes. Issue 8 (10th December 2015) - Pourgharibshahi, M.; Lambert, P.
Abstract : Despite six decades use of aluminum as a galvanic (sacrificial) anode, there remains a need for a better understanding of the underlying mechanisms for enhancing its efficient performance in cathodic protection systems. A few mechanisms have been proposed for the role of indium in the activation of Al‐Zn‐In anodes and there appears to be no general agreement on whether this element plays its depassivating role by modifying the bulk microstructure of the anode, chemical composition of its surrounding electrolyte or directly through doping the structure of the passive oxide film. These mechanisms have been critically reviewed to achieve a more comprehensive understanding of the role of indium in such applications. Moreover, the novel solidification processing called controlled diffusion solidification (CDS) has been introduced as an efficient way to surmount the poor castability of the anode alloy without any need for the addition of elements with detrimental effects on the electrochemical properties of the anode. Abstract : Since the middle of the 20th century, aluminum alloy galvanic or sacrificial anodes containing small additions of zinc and indium have been in regular use for the cathodic protection of submerged and buried steel in marine environments. The various mechanisms that have been suggested for the role of indium in maintaining the activity of such anodes has been reviewed.